2017
DOI: 10.2166/hydro.2017.076
|View full text |Cite
|
Sign up to set email alerts
|

Streamflow forecasting by combining neural networks and fuzzy models using advanced methods of input variable selection

Abstract: In this paper the performance of extreme learning machine (ELM) training method of radial basis function artificial neural network (RBF-ANN) is evaluated using monthly hydrological data from Ajichai Basin. ELM is a newly introduced fast method and here we show a novel application of this method in monthly streamflow forecasting. ELM may not work well for a large number of input variables. Therefore, an input selection is applied to overcome this problem. The Nash–Sutcliffe efficiency (NSE) of ANN trained by ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(13 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…The performance of the proposed hybrid model compared to that of least square SVM (LSSVM) model and the results were reported to be good. On this premise, an attempt towards the integration of ELM model with the genetic algorithm (GA) (an input selection algorithm) has been made by [30] for the forecasting of the monthly streamflow at the Ajichai Basin. The outcome of the study showed that the integration of ELM with GA enhanced the forecasting accuracy of the ELM model.…”
Section: Introductionmentioning
confidence: 99%
“…The performance of the proposed hybrid model compared to that of least square SVM (LSSVM) model and the results were reported to be good. On this premise, an attempt towards the integration of ELM model with the genetic algorithm (GA) (an input selection algorithm) has been made by [30] for the forecasting of the monthly streamflow at the Ajichai Basin. The outcome of the study showed that the integration of ELM with GA enhanced the forecasting accuracy of the ELM model.…”
Section: Introductionmentioning
confidence: 99%
“…ey are almost 1 for validation and more than 0.8 for all other cases. ese values are acceptable in the time-dependent highly nonlinear climate analyses [79][80][81][82]. However, out of them, LM algorithm has outperformed other training algorithms in the computational performance (highlighted in grey).…”
Section: Resultsmentioning
confidence: 99%
“…In the literature, there is a set of standard coefficients that provides agreement between measurements and predictions through a set of single parameter values. In most of the cases, authors report that their model is suitably based on the comparison of statistical parameters composed of measurement and model output data series by consideration one or few of the well-established agreement or association metrics among which are the most commonly used, accepted, and recommended ones are bias (BI), Percent Bias (PBI), coefficient of determination (R 2 ), mean square error (MSE) or root mean square error (RMSE), correlation coefficient (CC), Nash-Sutcliffe efficiency (NSE) and index of agreement (d) (Pearson 1895;Nash & Sutcliffe 1970;Willmott 1981;Santhi et al 2001;Gupta et al 2002;Moriasi et al 2007;Van Liew et al 2007;Özger & Kabataş2015;Tian et al 2015;Zhang et al 2016;Dariane & Azimi 2018).…”
Section: Introductionmentioning
confidence: 99%